Low-Voltage Electrical Installations : (IEC, 2002)
The particular requirements of this part of IEC 60364 apply to electrical installations in medical locations so as to ensure safety of patients and medical staff. These requirements, in the main, refer to hospitals, private clinics, medical and dental practices, health care centres and dedicated medical rooms in the work place